Um modelo informacional para gestão de operações: o caso da Cia. Vale do Rio Doce - Depto. de Manganês e Ferro-Ligas - Dias, Rogério de Matos (2003)
This research aims to theoretically develop an informationaI modeI able to provide a fully integrated supply chain management for multiplant manufacturing companies, as well as to prove its feasibility in the field, using a combined action-research and case study investigation methodology for a representative mining&metals company - Cia. Vale do Rio Doce, Manganese and Ferroalloys Departament. The study also intends to describe how the proposed model can provide planning and control capabilities for the operational, tactical and strategic decision making leveIs, as result of the transational and managerial processes automatization, data analysis agility and increasing in the quality decision making processes. Moreover, the study also intends to describe the contributions of that informationaI model for the supply chain management in similar companies as well as to generalize the model's application for similar multiplant manufacturing companies.